2017
DOI: 10.18203/2320-6012.ijrms20172431
|View full text |Cite
|
Sign up to set email alerts
|

A study to assess vaccine wastage in an immunization clinic of tertiary care centre, Gwalior, Madhya Pradesh, India

Abstract: Background: Vaccines are one of the most successful and cost-effective health intervention. It becomes imperative that use of vaccine was done through a proper framework of practical decision-making that confers positive health and economic benefits to the society of which Vaccine Wastage was a key factor. The aim of the study is to assess “Vaccine Wastage Rate” and “Wastage Factor” of different vaccines given to beneficiaries in Immunization Clinic and based on the above data, recommend measures to reduce it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
11
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 1 publication
3
11
1
2
Order By: Relevance
“…The current study reported high wastage for oral, lyophilized, and multi-dose vaccines. Similar results have also been observed in studies from various parts of the world [10,[15][16][17][18]. The current findings support that multi-dose vials with a multi-dose vial policy has less wastage compared to those without a multi-dose vial policy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The current study reported high wastage for oral, lyophilized, and multi-dose vaccines. Similar results have also been observed in studies from various parts of the world [10,[15][16][17][18]. The current findings support that multi-dose vials with a multi-dose vial policy has less wastage compared to those without a multi-dose vial policy.…”
Section: Discussionsupporting
confidence: 91%
“…Immunization averts vaccine-preventable diseases (VPD), and benefits indirectly through improving cognitive development, educational attainment, labour productivity, income generation, savings and investment. A study estimated that in low-income countries, for every dollar spent on immunization, 16 dollars are expected to be saved in healthcare costs, lost wages, and lost productivity due to illness and death [2].…”
Section: Introductionmentioning
confidence: 99%
“…1 The progress achieved by the program has brought undeniable benefits, despite still having to live with problems such as vaccine wastage, whether this be technical and/or physical wastage. 2 Some degree of wastage is inevitable, 3 and some of it is acceptable and justified. 2 The World Health Organization (WHO) estimates that globally vaccine wastage is around 50%, 4 while recommending minimum rates of 25% and 5% for multi-dose and single-dose vaccines, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…12 The present study shows that vaccine wastage rate was more for lyophilized vaccine (61.8% with a wastage factor of 2.61) as compared to liquid vaccine (41.3% with wastage factor 1.70 10-12.17 In the present study, wastage rate and wastage factor was more for injectable vaccines (wastage rate 54.7%, wastage factor 2. 20 Pentavalent, fractional IPV and JE being newly introduced vaccine, limited data are available regarding their wastage rate and wastage factor. In this study the wastage rate of Pentavalent vaccine and fractional IPV were 33.6% and 38.1% respectively which were higher than the proposed limit of 25% as recommended by Government of India as well as WHO for liquid vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…In similar studies by Gupta et al and Sharma et al the wastage rate of OPV was found to be 28.97% and 29.45% respectively 17,19. However studies by UNICEF, Palanivel et al and Mehta et al found much higher wastage rates for OPV which were 47%, 48.1% and 51.2% respectively whereas studies by Tiwari et al and Praveena et al showed much lower wastage rates of 14.65% and 2.4% respectively [10][11][12]14,20. The wastage rate for MR vaccine 56.3% in the present study.Since MR vaccine has been recently introduced in the National Immunization Schedule, limited studies are found regarding its wastage rate.…”
mentioning
confidence: 99%